1999
DOI: 10.1177/106907279900700402
|View full text |Cite
|
Sign up to set email alerts
|

Career Assessment on the Internet: An Exploratory Study

Abstract: In spite of the proliferation of job/career Web sites and the many articles and books discussing how to use these sites in job searching, we know of no research dealing with career assessment on the Internet. In an effort to remedy this deficit, the authors located a multitude of career sites containing a bewildering array of offerings. The research reported here focused on 24 Web career sites identified as having no-cost career assessment. While easy to use, the sites provided only a moderate degree of test i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 1 publication
0
35
0
Order By: Relevance
“…Oliver and Zack (1999) discuss how career counselors can use the WWW to conduct career assessments to assist clients with making effective decisions that are in keeping with the clients' overall career goals. Through their research, Oliver and Zack examined and evaluated a number of career-related sites on the WWW and discussed the types of information provided, ethical precautions taken, and potential benefits for clients.…”
Section: Practitioner Issuesmentioning
confidence: 99%
“…Oliver and Zack (1999) discuss how career counselors can use the WWW to conduct career assessments to assist clients with making effective decisions that are in keeping with the clients' overall career goals. Through their research, Oliver and Zack examined and evaluated a number of career-related sites on the WWW and discussed the types of information provided, ethical precautions taken, and potential benefits for clients.…”
Section: Practitioner Issuesmentioning
confidence: 99%
“…In regard to assessment, it is clear that many of the same psychometric standards (e.g., reliability, validity, norms) by which we evaluate non-Internet assessments also need to be applied to assessments given on the Internet. The importance of evaluating Internet-based tests is un-derscored by a recent review that indicated that most career tests on the Web were mediocre relative to professional standards (Oliver & Zack, 1999). Moreover, because an FTF or a paper and pencil assessment instrument has sound psychometric qualities, it cannot be assumed that an Internet version will have the same quality.…”
Section: Assessment and Counselingmentioning
confidence: 99%
“…Currently, the interpretations available on some sites are inadequate (Oliver & Zack, 1999). If access to counselors is not available, the caliber of interpretation becomes crucial.…”
Section: Career Assessment Measuresmentioning
confidence: 99%
“…As Jones (1999) stated, &dquo;in general, the Internet does not meet requirements for fixity that scholarship might require&dquo; (p. 7) and notes the complications this characteristic presents for rigorous research. Oliver and Zack (1999) reported that site changes-sometimes drastic onesrequired revisions of their ratings and their descriptions of some career assessment sites. In any event, researchers need to consider the impact of constant change and decide how to handle the difficulties it poses for research.…”
Section: Research Challenges Internet Changesmentioning
confidence: 99%
See 1 more Smart Citation